2021
DOI: 10.1007/978-1-0716-1685-7_6
|View full text |Cite
|
Sign up to set email alerts
|

Cell Free Remodeling of Glycosylation of Antibodies

Abstract: The N-glycosylation profile of a monoclonal antibody (mAb) is a critical quality attribute in relation to its therapeutic application. The control of this profile during biomanufacture is difficult because of the multiple parameters that affect the glycosylation metabolism within the cell and the environment in which the cell is grown. One of the approaches that can be used to produce a preferred glycan profile or a single glycoform is through chemoenzymatic remodeling during the isolation of a mAb. Here we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Studies have shown that the newly developed equipment can perform high-speed and accurate research on abnormal glycosylation (Bangarh et al, 2023 ). Although glycosylation accounts for 2–3% of the total mass of IgG antibodies, its therapeutic application is mainly attributed to the N-glycosylation profile of a monoclonal antibody (mAb) (Mota et al, 2022 ). The Mink CAdV-1 100 K protein has only one glycosylation site.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the newly developed equipment can perform high-speed and accurate research on abnormal glycosylation (Bangarh et al, 2023 ). Although glycosylation accounts for 2–3% of the total mass of IgG antibodies, its therapeutic application is mainly attributed to the N-glycosylation profile of a monoclonal antibody (mAb) (Mota et al, 2022 ). The Mink CAdV-1 100 K protein has only one glycosylation site.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the reported method is that N-glycans must be released by PNGaseF from denatured proteins to be a substrate for galactosidase. In 2018, Butler et al reported that a galactosidase from Bacteroides fragilis could remove terminal galactose directly from naïve antibody thus could be applied for high yields of single glycoform antibodies[20, 21]. However, all the previous studies on galactosidase activity were conducted in a non-cell system.…”
Section: Introductionmentioning
confidence: 99%